Ectrodactyly, Ectodermal Dysplasia, Cleft Lip, and Palate (EEC Syndrome) with Tetralogy of Fallot: A Very Rare Combination - Sharma, Deepak; Kumar, Chetan; Bhalerao, Sanjay; Pandita, Aakash; Shastri, Sweta; Sharma, Pradeep (Frontiers in Pediatrics, 2015)
Ectrodactyly, ectodermal dysplasia, and cleft lip/palate syndrome (EEC) syndrome is a rare genetic disorder with an incidence of around 1:90,000 live births. It is known with various names which includes split hand–split foot–ectodermal dysplasia–cleft syndrome or split hand, cleft hand or lobster claw hand/foot. We report first case of EEC with associated heart disease (Tetralogy of Fallot) who was diagnosed as EEC on the basis of clinical features and EEC was confirmed with genetic analysis.